基于IPC的插齿加工数控系统设计及插削斜齿的研究 - 韩江; 刘向前; 夏链; 何高清 (Jixie chuandong)
According to the theory of shaping gear, a way to carry out the shaping gear CNC based on MCX314 has been put up. Analyzing the systemic structure of hardware between MCX314、IPC and other parts. Designing the interface circuits and the holistic software of NC system upon MCX314. Utilizing servo system to accomplish the movements required, then achieving shaping the bevel gear completely digitally and imporving the machining accuracy of helical gear.